Kearifan Lokal Bahasa dan Sastra dalam Masyarakat Lintas Budaya - Manurung, Rosida Tiurma (Zenit, 2013)
National character empowering is essential to overcome threats, barriers, or challenges coming from outside that can threaten the sustainability and existence of local culture products. One of the efforts to maintain and strengthen national self identity is through language. Indonesian language is rich in the local values. The local color  that  presents the locality found in inter cultural communication reflects the Indonesian uniqueness.  Intercultural communication significantly reflects the atmosphere and location, philosophy, etnicity, uniqueness, beauty as well as national diversity. Intercultural communication conveys the richness of various ethnicities and exposes the local heritage that refers to local color, including the Indonesian national identity. Local values can be used as an effective tool to guide learners to become individuals with good behaviour and high morality as well as having a firm national character. This research discusses the learning process which can be used as an impetus to emplement local values with intercultural perspective, namely local values  with vision and mission which appreciate  diversity and plurality, democracy, humanism, and national character development  Keywords: local values, language learning, intercultural community, national character